Spatial variability of soil microbial biomass carbon in the Kuala Selangor coastline mangroves - Nooh, Nik Nurul Shahira (2017)
The rising levels of carbon dioxide (CO2) and other greenhouse gases is recognized as a serious environmental issue as it has caused global climate change. Mangrove forests are a part of a unique ecosystem that protects and stabilizes coastlines as well as mitigates the impact of climate change. Mangrove forests are also among the world’s most productive ecosystems, producing organic carbon well in excess of the ecosystem requirements and contributing significantly to the global carbon cycle. Soil microbial biomass are fundamentally important in ecosystem function as its primary roles is in governing the many nutrient cycling reactions which are essential in the maintenance of soil fertility. As such, the biomass is both a source and sink of the nutrients carbon, nitrogen, phosphorus and sulphur (C, N, P and S) contained in the organic matter. This study is aimed at determining the spatial variability map of soil microbial biomass C in the mangrove stands. 40 quadrant within the area of 80 m x10 m was formed. Soil samples at different depth which is 0-15 cm and 15-30 cm was taken to analyse for soil microbial biomass C. Geospatial analysis and spatial variability mapping was performed on each test variable.